Fourth Five-Year Plan Andhra Pradesh (1969-70 to 1973-74) Outline and Programmes - Planning Commission (Planning Commission, 1969)
The National Development Council decided in 1967 that the Forth Five-Year Plan should be formulated for the period 1969-74. With reference to this, the Planning Commission suggested in February, 1968 that the States may undertake a review of economic development and also take preliminary steps for formulating a Plan. Accordingly, we constituted 12 Working Groups for formulating the State’s Fourth Plan. The aggregate of the outlays recommended by these Working Groups came to Rs. 628 crores.
Planning and Co-operation Department, Government of Andhra Pradesh